Draft Annual Plan, 1993-94 Part II Government of Maharashtra - Planning Commission (Planning Commission, 1993)
Opening and Organisation of Ashram Shalas for Scheduled Caste, by Vol. (CSP) (District). Percentage to age group has been worked out on the population estimates supplied by Ministry of education new-Delhi under office. No. F. 8/4/85/5 at dated 28th February 1986 which have been received from the expert committee set up by the Registrar General The Central Governments Contribution to Special Loan Account is given to NABARD directly and not through the State Government. (This amount is included in the grand total).
Government of Maharashtra : Planning Department